Bus rapid transit using compensation method as bus priority system at isolated three-arm junction - Abd. Ramzi Sabli, 1994-, author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2019)
Thesis (Sarjana Kejuruteraan (Pengangkutan)) - Universiti Teknologi Malaysia, 2019